Improved functional and histochemical outcomes in l-DOPA plus tolcapone treated VMAT2-deficient mice. (15th December 2020) - Moreira, Carlos G.; Morawska, Marta M.; Baumann, Aron; Masneuf, Sophie; Linnebank, Michael; Sommerauer, Michael; Landolt, Hans-Peter; Noain, Daniela; Baumann, Christian R.
Abstract: Parkinson disease is typically treated with L-3, 4-dihydroxyphenylalanine (or levodopa) co-prescribed with concentration stabilizers to prevent undesired motor fluctuations. However, the beneficial role of the chronic combined therapy on disease progression has not been thoroughly explored. We hypothesized that tolcapone, a catechol-O-methyl-transferase inhibitor, co-administered with levodopa may offer beneficial long-term disease-modifying effects through its dopamine stabilization actions. Here, we followed vesicular monoamine transporter 2-deficient and wild-type mice treated twice daily per os with vehicle, levodopa (20 mg/kg), tolcapone (15 mg/kg) or levodopa (12.5 mg/kg) + tolcapone (15 mg/kg) for 17 weeks. We assessed open field, bar test and rotarod performances at baseline and every 4th week thereafter, corresponding to OFF-medication weeks. Finally, we collected coronal sections from the frontal caudate-putamen and determined the reactivity level of dopamine transporter. Vesicular monoamine transporter 2-deficient mice responded positively to chronic levodopa + tolcapone intervention in the bar test during OFF-periods. Neither levodopa nor tolcapone interventions offered significant improvements on their own. Similarly, chronic levodopa + tolcapone intervention was associated with partially rescued dopamine transporter levels, whereas animals treated solely with levodopa or tolcapone did not present this effect. Interestingly, 4-month progression of bar test scores correlated significantly with dopamine-transporter-label density. Overall, we observed a moderate functional and histopathological improvement effect by chronic dopamine replacement when combined with tolcapone in vesicular monoamine transporter 2-deficient mice. Altogether, chronic stabilization of dopamine levels by catechol-O-methyl-transferase inhibition, besides its intended immediate actions, arises as a potential long-term beneficial approach during the progression of Parkinson disease. Highlights: Co-administration of levodopa and COMT inhibitor Tolcapone. Stabilization and equalization of levodopa concentration in Parkinson mouse model. Assessment of histopathological and behavioral outcomes in relation to treatments. Improvement of histopathological state in levodopa + Tolcapone-treated mice. Ameliorated behavioral performance in stabilized levodopa group.